Internal and external factors influencing fashion design characteristics among undergraduate fashion design students - Armina Sari Harahap; Resmi Darni; Weni Nelmira; M. Giatman; Fadhillah Riski Aisyah Nasution; Nanda Sari Siregar (Global Econedu, 2026)
This study aimed to examine the effects of internal and external factors on students' fashion design characteristics in the Women's Fashion Design course. An explanatory quantitative study with a correlational design was conducted involving 30 fourth-semester students from the Fashion Design Vocational Education Study Program at Universitas Aufa Royhan Padangsidimpuan using total sampling. Internal and external factors were measured through validated questionnaires, while fashion design characteristics were assessed using a performance-based rubric. Data were analyzed using multiple linear regression. Internal factors significantly influenced fashion design characteristics (β = 0.613, t = 5.613, p < 0.001), as did external factors (β = 0.374, t = 3.424, p = 0.002). Simultaneously, both variables significantly predicted fashion design characteristics (F = 82.314, p < 0.001; Adjusted R² = 0.849). Strengthening students' internal competencies alongside supportive learning environments is essential for improving creativity and the quality of fashion design outcomes